Computer programs for the organization of medical bibliography. - Gozalo Reques F; González Pascual AL; Estrada Rodríguez JL; García-Norro Herreros FJ (Rehabilitación, 2000)
The bibliography search is an important part of the work of the physician nowadays. On the other hand, the widespread use of the computer, the lessening of the price of the modem and the free access to medical data bases (for example, the popular Medline) have made it possible to carry out online searches, both in ones work site as well as in their own home. These data bases are, in our times, one of the most interesting resources that WWW offers to the physician who investigates or publishes or who, simply, wants to keep up to date. However, the handling of the information obtained in this way frequently takes much time and effort. In this article, we offer the physician practical advise on the bibliographic organization downloaded from Internet and a critical assessment of the software of the bibliographic organization that is presently available on the international market.